Pemberdayaan Perempuan dalam Proses Pembuatan Black Garlic menuju Masyarakat Mandiri di Era Ekonomi Industri 4.0 - Sri Mujiarti Ulfah; Solikah Nurwati; Suprayitno Suprayitno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Kahayan Market in Palangka Raya is more famous as a market for herbal medicines. The benefits of single black garlic are familiar, but for the people of the city of Palangka Raya, the single black garlic is still unfamiliar. Black garlic is known to have higher anticancer content than ordinary garlic, as well as anti-bacterial activity. The many properties possessed by black garlic, provide space for people to consume herbal medicines as well as considerable opportunities to become businesses. Seeing the high enthusiasm of the participants involved in the training activities of making black garlic it can be concluded that the training participants were greatly helped by the existence of this training. Participants can absorb training material and immediately practice making black garlic well. After the training activity, the participants were able to make quality products in the form of black garlic. With the high response from the participants and also the products produced, it can be concluded that the training activities for making black garlic were successfully carried out well. The suggestion of this activity is the need for ongoing monitoring related to the manufacture of Black Garlic going forward, it is necessary to increase the spread of market share targets to increase product sales, as well as the need for broader cross-sector collaboration to increase the productivity of black garlic going forward